Egypt - Next Step Recommendations for Affordable Housing Policy and the National Housing Program : Mortgaged-Linked Subsidies and Housing Supply considerations - World Bank (Washington, DC, 2012)
At the request of the Government of Egypt (GOE), the objective of this brief note is to provide concise recommendations on next steps for the National Housing Program (NHP). These recommendations and policy analysis are an elaboration of the framework for housing policy reform in urban areas in Egypt, a draft of which was endorsed by the Ministry of Housing, Utilities and Urban Development (MHUUD) and the Ministry of Investment (MOI) in the high-level policy workshop held in September 2007. The Framework, an evolving strategy building blocks document, proposed a set of comprehensive housing sector reforms and improvements to the NHP consisting of five action channels - unlocking the vacant housing stock, creating a fluid rental market, enhancing affordability through improved access to housing finance and reduction of formal housing supply cost, improved targeting of subsidies, and transforming the government's role into an enabler of the housing market. During the Ministerial workshop in September 2007, it was agreed that the four priority actions were: (i) the design and implementation of a housing information system; (ii) mainstreaming the use of demand-based mortgage-linked subsidy instruments; (iii) set up of a high-level housing policymaking body to coordinate and rationalize the interventions of the different concerned stakeholders; and (iv) expansion of the Housing Demand Study to other areas of Egypt. United States Agency for International Development or USAID Second Technical Assistance for Policy Reform, or TAPRII has completed the design of the housing information system and has made significant progress in the expansion of the housing demand survey. The World Bank's technical assistance to the GOE, reflected in this note and follow up work, focused on strengthening the housing policymaking process and subsidy policy and expanding the mortgage linked subsidy program.